A new algorithm and routing protocol based on convolutional codes using TCNet: Trellis Coded Network - F. Lima Filho, Diogo; Roberto Amazonas, José (EAI Endorsed Transactions on Internet of Things, 2017)
Currently emerging technologies have taken advantage of the possibility of communication with the World Wide Web to expand to all applications of this technology, among them the Internet of Things – IoT. This work proposes the implementation of new packets forwarding algorithms using the concept of convolutional codes. The results obtained by means of extensive simulations show gains in terms of latency and energy consumption reduction compared to the AODV protocol. The implementation complexity is extremely low and compatible with the few hardware resources usually available in the elements of a wireless sensor network (WSN). This research uses Finite State Machine (FSM) to get the networks nodes, obtained from settings with Mealy machine – (MM) due to the low complexity of (“XOR” gates and "shift registers"), eliminating the use of any routing tables by means of Trellis decoding. The route can be chosen based on criteria of Quality of Service (Qos) – aware routing protocols.